SABR for Baskets. Issue 112 (1st April 2021) - Hagain, Patrick S.; Lewsniewski, Andrew S.; Skoufis, G. G.; Woodward, E.
Abstract : We show that a basket of assets, each governed by the normal SABR model, is also governed by the normal SABR model. Explicit formulae for the SABR parameters of the basket are derived from the SABR parameters of the basket constituents.